Philippine-Japan Economic Linkages: A Case Study of Cebu - Victorina Zosa (Philippine Institute for Development Studies (PIDS), 2004)
The impact of the Japan-Philippine Economic Agreement(JPEPA) can be enriched by providing a regional dimension in its macro-analysis. Cebu-Japan cooperation largely hinges on Cebus economic competitiveness which manifests itself through its quality human resources, its dynamic export sector and tourism industry, its proximity to international entry and exit points, its infrastructures, its cost of doing business, its quality of life and the responsiveness of LGU to business needs. On the other hand, Cebu, as a destination of Japanese investments, is hampered by the relatively high wages of both unskilled and skilled labor, an unstable wage rate environment and moderately high costs of telecommunication, water, gas, and container transport. With this, the exercise on cost-benefit analysis yielded positive gains for Cebus economy. The foreign exchange loss, driven by the balance of trade deficit between Cebu and Japan, and the foregone corporate income taxes were offset by the Japanese direct investments, salaries and mandatory contributions of Cebu Economic Zones (CEZ) employees, income for Japanese tourists, remittances of OCWs in Japan, estimated cost-of-living expenses of Japanese nationals residing in Cebu and the Japanese ODA to Cebu.
Keywords: 330; investment; human resources; bilateral agreements; economic linkages; economic competitiveness; Internationale Wirtschaftsbeziehungen; Freihandelszone; Handelsliberalisierung; Arbeitsmobilität; Auslandsinvestition; Internationaler Wettbewerb; Japan; Cebu; Philippinen